PIROLISIS CAMPURAN BIOMASSA LIMBAH SEKAM PADI DAN LIMBAH PLASTIK LOW DENSITY POLYETHYLENE MENGGUNAKAN KOMPOR BIOMASSA - Muhammad Rifqi Koes Setyawira; Danar Susilo Wijayanto; Ngatou Rohman (Nozel : Jurnal Pendididikan Teknik Mesin, 2023)
The demand for fuel oil is increasing day by day, resulting in the depletion of oil and gas reserves in Indonesia. Rice husk waste biomass and low-density polyethylene plastic are wastes that can be utilized as alternative fuel sources by pyrolysis method. Pyrolysis is the process of burning organic and synthetic materials in conditions of little or no oxygen by utilizing heat from high temperature combustion. Pyrolysis method processing requires a heater to burn the material during the process. Efforts that can be made are the use of biomass stoves as the right solution because of the availability of abundant and cheap raw materials, biomass stoves can also provide solutions to reduce the impact of environmental pollution smoke. The purpose of this study was to determine the temperature produced by the biomass stove and the effect of the comparison of the composition of the biomass mixture of rice husk waste and low density polyethylene plastic waste on the quantity of pyrolysis oil. This research uses experimental method with quantitative descriptive analysis technique. This research was conducted by pyrolyzing a mixture of rice husk biomass waste and low density polyethylene plastic waste with variations in composition ratio of 0%:100%, 25%:75%, 50%:50%, 75%:25%, and 100%:0%. The pyrolyzed oil was then filtered and tested for quantity. The test results show that the biomass stove can be used as a heater in a pyrolysis device with a capacity of 4 kg of coconut shell briquettes. The use of coconut shell briquettes as fuel has the advantage of being able to produce higher heat and last longer than charcoal. The biomass stove can produce the highest pyrolysis temperature reaching 665.5°C at the bottom, 541°C in the middle, and 430.3°C at the top. There is an effect of variation in the composition of the mixture of rice husk waste and low-density polyethylene plastic waste on the quantity of pyrolysis oil. The composition of more rice husk waste compared to low density polyethylene plastic waste produces less quantity of pyrolysis oil, while the comparison of the composition of more low density polyethylene plastic waste compared to rice husk waste produces pyrolysis oil with more quantity. This can be seen from the quantity of pyrolysis oil produced ranging from 265 ml to 853.3 ml.